Chemical and physical pretreatments of fruits and vegetables: Effects on drying characteristics and quality attributes - a comprehensive review - Deng, Li-Zhen; Mujumdar, Arun S.; Zhang, Qian; Yang, Xu-Hai; Wang, Jun; Zheng, Zhi-An; Gao, Zhen-Jiang; Xiao, Hong-Wei (Critical reviews in food science and nutrition, 2019)
Pretreatment is widely used before drying of agro-products to inactivate enzymes, enhance drying process and improve quality of dried products. In current work, the influence of various pretreatments on drying characteristics and quality attributes of fruits and vegetables is summarized. They include chemical solution (hyperosmotic, alkali, sulfite and acid, etc.) and gas (sulfur dioxide, carbon dioxide and ozone) treatments, thermal blanching (hot water, steam, super heated steam impingement, ohmic and microwave heating, etc), and non-thermal process (ultrasound, freezing, pulsed electric field, and high hydrostatic pressure, etc). Chemical pretreatments effectively enhance drying kinetics, meanwhile, it causes soluble nutrients losing, trigger food safety issues by chemical residual. Conventional hot water blanching has significant effect on inactivating various undesirable enzymatic reactions, destroying microorganisms, and softening the texture, as well as facilitating drying rate. However, it induces undesirable quality of products, e.g., loss of texture, soluble nutrients, pigment and aroma. Novel blanching treatments, such as high-humidity hot air impingement blanching, microwave and ohmic heat blanching can reduce the nutrition loss and are more efficient. Non-thermal technologies can be a better alternative to thermal blanching to overcome these drawbacks, and more fundamental researches are needed for better design and scale up.